THE PERCEPTION OF YOUNG ROMANIANS ON EXPERIENTIAL MARKETING - Corina Paula TARŢA (Management & Marketing)
Today’s consumers have built around themselves a protective shield against the hundreds of ads they are being bombarded with each day. In this sense, the companies have chosen to direct their focus towards unconventional advertising, particularly towards providing the consumer with a direct relationship with the product. Experiential marketing is the business philosophy which represents the basis for bringing the consumer together with the product; it is a method to which the individuals cannot remain indifferent, as it implies their involvement in the actual action. The purpose of this research has been identifying the perceptions of young Romanians on experiential marketing campaigns used abroad, and determining the degree to which these campaigns would influence their decisions to buy and if it would change their perception of the brand. The advantage of using this method is that it offers the consumer a long-lasting image and it creates a holistic experience which integrates sensory, affective, cognitive, behavioral and social experiences.